2021
DOI: 10.1002/ase.2037
|View full text |Cite
|
Sign up to set email alerts
|

Instructional Approaches: Anatomy Education of Physical Therapists

Abstract: The profession of physical therapy has undergone an evolution since its inception. Since the early 1900s it has grown from a technical training program to a doctorate level degree. Human anatomy courses remain a requirement for physical therapist educational curricula. However, changes in anatomy pedagogy have been trending within health profession educational models, leading to questions regarding which method is best for student learning. The objective of this study was to determine if anatomy instructional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 108 publications
(216 reference statements)
0
16
0
Order By: Relevance
“…The results of a survey administered to physicians revealed that human anatomy was considered the most relevant course for clinical practice, specifically for physical examination and therapeutic procedures (Arráez-Aybar et al, 2010). Simons et al (2020) also determined that licensed physical therapists who learned the head and abdominal anatomy via dissection laboratories had more anatomical knowledge for those regions compared to those therapists who learned by other means (prosection, plastination, technology or no laboratory instruction). However, in the same paper, the authors found that instructional methods did not impact the knowledge of anatomy for the upper and lower extremities, pelvis and spine in licensed physical therapists (Simons et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The results of a survey administered to physicians revealed that human anatomy was considered the most relevant course for clinical practice, specifically for physical examination and therapeutic procedures (Arráez-Aybar et al, 2010). Simons et al (2020) also determined that licensed physical therapists who learned the head and abdominal anatomy via dissection laboratories had more anatomical knowledge for those regions compared to those therapists who learned by other means (prosection, plastination, technology or no laboratory instruction). However, in the same paper, the authors found that instructional methods did not impact the knowledge of anatomy for the upper and lower extremities, pelvis and spine in licensed physical therapists (Simons et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Further, no uniform international standard for entry-level PTE exists concerning the degree required, while the program types and lengths vary widely (WCPT, 2011;Moffat, 2012;Adam et al, 2013;FAP, 2016;Barradell, 2017;Shead et al, 2018). As a result, despite the long-standing history of including anatomy education within PTE, no consensus exists regarding how much is needed, what specific content should be included, or how anatomy should be taught (McKenzie and Gutierrez, 2007;Youdas et al, 2015;Shead et al, 2016Shead et al, , 2018Blum et al, 2020;Simons et al, 2022).…”
Section: Physical Therapy and Anatomy Educationmentioning
confidence: 99%
“…Since that time, the number of papers published that are specific to anatomy coursework or content as it relates to PTE or practice is negligible (Donovan, 1994;Armstrong and Rosser, 1996;Fiebert and Waggoner, 1996;Latman and Lanier, 2001;Reimer et al, 2013;Shead et al, 2016Shead et al, , 2018. Most often, the research studies survey anatomy educators in PTE programs or clinicians regarding faculty credentials, teaching modalities, student perceptions, or comparisons between other healthcare professions (Berube et al, 1999;Plack, 2000;Latman and Lanier, 2001;Hamilton et al, 2008;Livingston et al, 2014;Simons et al, 2022). To date, no prospective investigation regarding the integrity of anatomical competence needed for physical therapy practice has been conducted.…”
Section: Creating a Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies report on the instructional and/or assessment approaches in physical therapy courses (Green et al, 2014; Green & Whitburn, 2016; McDonald et al, 2021; Melguizo et al, 2007; Shead et al, 2018; Simons et al, 2022; Youdas et al, 2015) but not on the actual content that is taught. A scoping review of curricular and pedagogical features of anatomy teaching for undergraduate physical therapy courses identified that while there are many accounts of anatomy educational approaches, only three of the 54 included studies reported curriculum content (Shead et al, 2020).…”
Section: Introductionmentioning
confidence: 99%